Implementation of MALDI MS profiling and imaging methods for the analysis of real crime scene fingermarks. Issue 9 (7th April 2017) - Bradshaw, R.; Denison, N.; Francese, S.
Abstract : First insights into MALDI MS based method's transition to operational casework involving fingermark analysis. Abstract : In the study presented here, four examples of crime scene fingermarks analysed by Matrix Assisted Laser Desorption Ionisation Mass Spectrometry Imaging (MALDI MSI), in collaboration with the local Police Force, are reported. These marks are associated to high profile crimes such as drug dealing, murder and harassment. Following the application of forensic enhancement techniques by the CSI or the crime lab, one of the marks could be directly analysed on the surface of deposition and the others were analysed as primary lifts. In one case, no physical or molecular information was obtained whereas in two cases both ridge detail (albeit not useful for identification purposes) and molecular information could be retrieved. In one case, the intelligence gathered around the suspect's state of mind is, to date the most accomplished demonstration of the benefits and the operational feasibility MALDI MS based methods. These four casework examples are to be considered a first insight into the limitations, benefits and feasibility of MALDI MS based methods in the field; due to the extreme variability in the state of the mark, comprehensive evaluation of these aspects can only be undertaken upon the analysis of a large number of crime scene marks. However, this work does represent a significant advancement, compared to previous published work, as it demonstrates operational feasibility, with different levels of success, despite uncontrollable, unknown and unaccountable environmental and donor variability.